“Geographical Imaginaries”: A Three-Decade Literature Review of Usage and Applications Across Academic Contexts - Luczaj Kamil (Open Cultural Studies, 2025)
This article seeks to examine and categorize the varied uses of the term geographical imaginaries within the broader fields of the social sciences and humanities. Like related concepts such as spatial imaginaries, geographical imaginations, and imaginative geographies, the term gained traction in the early 2000s and has grown in prominence since. Following PRISMA guidelines, this literature review is based on an analysis of 116 articles containing the phrase geographical imaginaries, retrieved from the Scopus database. The corpus was carefully screened according to eligibility criteria. Through selected excerpts and interpretative commentary, the review aims to contextualize how geographical imaginaries are employed across different studies. The findings confirm earlier assumptions that the term is often used loosely. Approximately half of the analyzed articles relied on a generic, commonsense understanding of the term. Moreover, even when a more rigorous definition – rooted in established literature and supported by clear criteria – was employed, its application was not always consistent or methodologically robust. Finally, the review identifies the diverse research contexts in which geographical imaginaries are invoked and distinguishes between different types of imaginaries based on their scope and range.